2020
DOI: 10.3390/w12123525
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of AnnAGNPS Model for Runoff Simulation on Watersheds from Glaciated Landscape of USA Midwest and Northeast

Abstract: Runoff modeling of glaciated watersheds is required to predict runoff for water supply, aquatic ecosystem management and flood prediction, and to deal with questions concerning the impact of climate and land use change on the hydrological system and watershed export of contaminants of glaciated watersheds. A widely used pollutant loading model, Annualized Agricultural Non-Point Source Pollution (AnnAGNPS) was applied to simulate runoff from three watersheds in glaciated geomorphic settings. The objective of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…Final values varied by watershed: calibrated CN was adjusted from baseline values by -7 units (North Fork), -5 units (Main Stem), and +6 units (Irish Creek), and calibrated initial soil moisture values were 0.7 (North Fork), 0.4 (Main Stem), and 0.8 (Irish Creek). These magnitudes of CN adjustment used to calibrate AnnAGNPS were consistent with Tamanna et al (2020), who adjusted contoured row crop CN by +6 to -7 with different adjustments for each of their three study watersheds, Karki et al (2017), who adjusted row crop CN by -9, and Parajuli et al (2009), who adjusted cropland CN by +4 to -4.…”
Section: Streamflowsupporting
confidence: 60%
“…Final values varied by watershed: calibrated CN was adjusted from baseline values by -7 units (North Fork), -5 units (Main Stem), and +6 units (Irish Creek), and calibrated initial soil moisture values were 0.7 (North Fork), 0.4 (Main Stem), and 0.8 (Irish Creek). These magnitudes of CN adjustment used to calibrate AnnAGNPS were consistent with Tamanna et al (2020), who adjusted contoured row crop CN by +6 to -7 with different adjustments for each of their three study watersheds, Karki et al (2017), who adjusted row crop CN by -9, and Parajuli et al (2009), who adjusted cropland CN by +4 to -4.…”
Section: Streamflowsupporting
confidence: 60%
“…However, it is limited to a single rainfall simulation and cannot evaluate the long-term impact of nonpoint-source pollution in the basin. The Annualized Agricultural Non-Point Source (AnnAGNPS) model (Tamanna et al, 2020) is based on this model and can be employed to evaluate surface runoff, sediment erosion, and nitrogen and phosphorus loss in the basin. This model is capable of simulating both the long-term runoff and sediment quantity of the basin and the runoff and sediment transport process within the watershed at multiple scales.…”
Section: Empirical Statistical Modelsmentioning
confidence: 99%
“…In general, this information is missing from most REMM studies, which can hinder the ability of REMM to properly predict riparian functions at the site scale [39]. To offset this issue, a field-scale hydrological model, Annualized AGricultural Non-Point Source (AnnAGNPS), was used to predict the runoff and sediment loading to the riparian buffer [44,45]. AnnAGNPS [46,47] is a daily time step, watershed scale, pollutant-loading, distributed model developed to simulate long-term runoff, sediment, nutrients, and pesticide transport from agricultural watersheds [48][49][50].…”
Section: Upland Inputs (*Fin File)mentioning
confidence: 99%
“…For this study, AnnAGNPS was used with a cell size of 1.8-0.4 km 2 (interquartile range, IQR = Q 3 − Q 1, of cell size among a total of 185 cells in the watershed) to simulate input cells representing upland inputs to each of the eight riparian buffers within upper Pawcatuck River watershed. Details of the application of AnnAGNPS model on the study area can be found in our companion study [45]. Table 1 represents the upland characteristics for all the riparian sites.…”
Section: Upland Inputs (*Fin File)mentioning
confidence: 99%